Disappearance of squeezed back-to-back correlations: a new signal of hadron freeze-out from a supercooled quark gluon plasma - Csörgo, T. [UNESP]; Padula, Sandra S. [UNESP] (Sociedade Brasileira de Física, 2007)
We briefly discuss four different possible types of transitions from quark to hadronic matter and their characteristic signatures in terms of correlations. We also highlight the effects arising from mass modification of hadrons in hot and dense hadronic matter, as well as their quantum statistical consequences: the appearance of squeezed quantum states and the associated experimental signatures, i.e., the back-to-back correlations of particle-antiparticle pairs. We briefly review the theoretical results of these squeezed quanta, generated by in-medium modified masses, starting from the first indication of the existence of surprising particle-antiparticle correlations, and ending by considering the effects of chiral dynamics on these correlation patterns. Nevertheless, a prerequisite for such a signature is the experimental verification of its observability. Therefore, the experimental observation of back-to-back correlations in high energy heavy ion reactions would be a unique signature, proving the existence of in-medium mass modification of hadronic states. on the other hand, their disappearance at some threshold centrality or collision energy would indicate that the hadron formation mechanism would have qualitatively changed: asymptotic hadrons above such a threshold are not formed from medium modified hadrons anymore, but rather by new degrees of freedom characterizing the medium. Furthermore, the disappearance of the squeezed BBC could also serve as a signature of a sudden, non-equilibrium hadronization scenario from a supercooled quark-gluon plasma phase.
Keywords: Correlations; Femtoscopy; Quantum optics; Squeezed coherent states; Particle-antiparticle pairs